A microscopy approach for in situ inspection of the μCMM stylus for contamination - Feng, Xiaobing; Pascal, Jonathan; Lawes, Simon (IOP Publishing, 2017)
During the µCMM measurement process, contamination gradually builds up on the surface of the stylus tip and affects dimensional accuracy of the measurement. Regular inspection of the stylus for contamination is essential in determining the appropriate cleaning interval and preventing the dimensional error from becoming significant. However, in situ inspection of a µCMM stylus is challenging due to the size, spherical shape, material and surface properties of a typical stylus. To address the challenges, this study evaluates several non-contact measurement technologies for in situ stylus inspection and based on those findings proposes a cost-effective microscopy approach. The operational principle is then demonstrated by an automated prototype, coordinated directly by the CMM software MCOSMOS, with an effective threshold of detection as low as 400 nm and large field of view and depth-of-field. The level of stylus contamination on the stylus has been found to increase steadily with the number of measurement contacts made. Once excessive contamination is detected on the stylus, measurement should be stopped and stylus cleaning procedure should be performed to avoid affecting measurement accuracy.